Resíduo seco do processamento do tomate na dieta de coelhos e seus reflexos sobre o desempenho, carcaça e qualidade de carne. - Cavalcanti, Cácio Ribeiro (2017)
The objective of this study was to evaluate the inclusion of dry tomato processing residue in complete diets for growing rabbits on the productive performance, diets digestibility, carcass characteristics and meat sensory analysis. For this purpose, 60 New Zealand White rabbits were weaned at 30 days of age, with a mean initial weight of 0.6294 ± 0.019 kg, distributed in a DIC, two animals per experimental unit. They were distributed in five treatments (0, 5, 10, 15 and 20% inclusion of the dry tomato processing residue) and six replicates. Diets were formulated to meet the nutritional requirements of rabbits. During the performance test, the digestibility of the diets was performed, when the animals reached 55 days of age, where the faeces were collected. The animals received water and ad libitum feed, reaching the end of the experiment (85 days) were slaughtered. The parameters evaluated were: Initial and final weight, mean feed intake, mean daily gain, feed conversion, warm and cold carcass weight, carcass yields, thoracic cervical region, forepaws (paleta) and hindquarters (muscle Biceps femoris), relative weights of the heart, liver, fat Visceral and kidneys. For those of digestibility: dry matter, crude protein, crude energy, NDF and FDA. For meat quality, pH, color and sensorial analysis were evaluated. The data were submitted to analysis of variance, and in case of differences regression analysis was applied. The animals presented a difference in performance withfinal weight and GMD; Digestibility: NDF, FDA and dry matter; Carcass quality: cold carcass weight, pH 45 minutes and pH 12 hours; And sensory analysis: appearance and aroma. According to the research, it is recommended to include levels of less than 5% of the dry tomato processing residue in diets for white New Zealand rabbits, aiming at not impairing the final weight, average daily gain, diets digestibility, weight Of cold housing and housing pH.